Respons Pertumbuhan Bibit Kakao (Theobroma cacao L.) terhadap Aplikasi Pupuk NPK dan Kascing pada Media Tanam Ultisol - Wulan Kumala Sari; Intan Alfrizon (Soilrens, 2023)
Ultisols are a marginal soil order which is widespread in Indonesia. However, due to the limitations the fertility of this soil, it is necessary to add organic matter beside inorganic fertilizers to support the growth of cacao seedlings. The objectives of this study were to determine the growth response of cacao seedlings due to the application of NPK and vermicompost fertilizers, as well as to determine the interaction effect and the best dosage of those fertilizers on the growth of cacao seedlings in Ultisols. This study was designed in a Completely Randomized Design (CRD) Factorial with two treatment factors. Treatment doses for NPK were 0 g/polybag, 0,5 g/polybag, and 1 g/polybag, while the doses for vermicompost treatment were 0 g/polybag, 12,5 g/polybag, and 25 g/polybag. Each of these factors was repeated three times, so 27 experimental units in total. Observational data were analyzed using analysis of variance and further analyzed by Duncan’s New Multiple Range Test (DNMRT) at 5% significance level for statistically significant results. The growth variables of cacao seedlings were seedling height, stem diameter, number of leaves, and leaf area index. The results showed that the best dose of vermicompost fertilizer to the growth response of cacao seedlings was 12,5 g/polybag. However, we found no interaction effect between NPK fertilizer and vermicompost to the growth of cacao seedlings in Ultisols